Anxiety and Maternal Fetal Attachment - Evi Wahyuntari; Ika Puspitasari (International Journal of Health Science and Technology, 2020)
Maternal Fetal Attachment and fetal growth are strongly influenced by the emotional state or anxiety of the mother, this can be seen from the psychological condition of the mother before giving birth.  The psychological condition of the mother will have an impact on the health and development of the fetus. In Indonesia, there are about 28.7% of pregnant women who experience anxiety in the third trimester. The research objective was to determine the relationship between anxiety and maternal fetal attachment. Cross sectional study. With a population of pregnant women in the third trimester aged 20-35 years as many as 42 respondents. The sampling technique used non probability sampling with a total sampling of 42 pregnant women in the third trimester. The anxiety measurement tool uses the Zung self-rating anxiety scale (ZSAS) questionnaire and the MFA uses the Prenatal attachment inventory (PAI) questionnaire. Pearson analysis (product moment). The p value is 0.023 with a correlation coefficient of -0.350. The conclusion is that there is a relationship between anxiety and maternal fetal attachment at Gamping II Public Health Center with weak relationship closeness, it means that the lower the anxiety score received, the higher the maternal fetal attachment score. Suggestions for pregnant women in the third trimester to be more active in seeking information, both electronic print media, health workers and others about maternal-fetal attachment since pregnancy.